Comparative Metabolite Profiling and Fingerprinting of Mature and Immature Grains of Different Species using a Multiplex Approach of LC-MS and GC-MS Coupled to Chemometrics - Saied, Doaa Bahaa Abdelhalim (AUC Knowledge Fountain, 2023)
The objective of the current study was the assessment of heterogeneity amongst metabolites of 5 cereal and leguminous grains of different species, and cultivars i.e., Triticum aestivum L., Hordeum vulgare L., Vicia faba L. & Cicer arietinum L. at different maturity stages. Gas chromatography mass-spectrometry (GC-MS) post silylation technique was employed for nutrients profiling. A total of 70 peaks belonging to sugars, fatty acids/esters/steroids and organic acids were identified including sucrose, melibiose, glucose and fructose as major sugars, butyl caprylate, hydroxybutanoic acid and malic acid to contribute for the discrimination between grain species and different maturity stages. Ultra-performance liquid chromatography tandem mass- spectrometry (UPLC-MS/MS) was further applied for secondary metabolites’ profiling. A total of 147 peaks were annotated from various classes viz. sugars, oxylipids, flavonoids, amino acids/peptides, terpenoids, and alkaloids. Datasets from both techniques were coupled to chemometric analysis for better processing and identification of markers. Molecular networking was applied in UPLC-MS dataset for better visualization and cluster segregation. DPPH and FRAP assays were attempted to correlate antioxidant results to secondary metabolites’ variation upon maturation.